2017
DOI: 10.1177/1740774517737318
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Federal Drug Administration Docket for community consultation and public disclosure in exception from informed consent trials

Abstract: The public information contained in the Docket varies broadly by trial and content. Additionally, as evidenced by the wide range of the Docket Review Content Score, submission guidelines are not followed uniformly. Given the apparent uncertainty about what should be submitted, and the need for best practice recommendations, it is valuable to categorize and summarize existing community consultation and public disclosure content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Recognizing and honoring local variation in implementing CC and PD may be crucial to optimize these processes locally. A 2018 study systematically reviewed FDA-reported CC and PD activities for 34 trials 27 , indicating similar variability as our study, and concluded that there is a need to identify best practices and less uncertainty as to the implementation of CC and PD. With the current local variation in implementing CC and PD processes, there may be misunderstandings of what is required for CC and PD between local and centralized IRBs.…”
Section: Discussionsupporting
confidence: 72%
“…Recognizing and honoring local variation in implementing CC and PD may be crucial to optimize these processes locally. A 2018 study systematically reviewed FDA-reported CC and PD activities for 34 trials 27 , indicating similar variability as our study, and concluded that there is a need to identify best practices and less uncertainty as to the implementation of CC and PD. With the current local variation in implementing CC and PD processes, there may be misunderstandings of what is required for CC and PD between local and centralized IRBs.…”
Section: Discussionsupporting
confidence: 72%
“…More work is needed to understand the gamut of community consultation activities and public disclosure activities that are documented and submitted to the FDA. One recent review of material submitted to the FDA docket 95S-0158 4 attempted to catalog these activities. However, that review examined online material only (with 177 official documents containing 6998 pages) rather than the full docket available by in-person request (with 177 official documents and 289 draft documents containing 15 958 pages at the time of this review).…”
Section: Discussionmentioning
confidence: 99%
“…We started with the trial samples identified by Klein et al, 7 Feldman et al, 8 Armstrong et al, 9 and Dhamanaskar & Merz. 12 We then examined the papers in the reviews of community engagement activities conducted in support of EFIC trials by Haggins et al, 10 and Dickert et al 11 as an indirect way of identifying trials. Other articles and reviews were examined to ensure we were capturing proposed and completed EFIC trials.…”
Section: Methodsmentioning
confidence: 99%
“…They identified 34 trials. 10 Most recently, Neal Dickert and colleagues performed a scoping review, identifying 27 articles reporting results of community engagement activities for planned EFIC trials. 11…”
mentioning
confidence: 99%